NEUROPSYCHOLINGUISTIC CONCEPTS (Scientific journal of the Fergana State University, 2025)
The article examines neuropsycholinguistic concepts that combine the achievements of neuroscience and psycholinguistics to analyze speech and language processes. Key approaches to studying how the brain processes language information are discussed, including the mechanisms of perception, production, and understanding of speech. Particular attention is paid to the theory of neural network modulation and the role of the cerebral cortex in language processes. The article also analyzes experimental data confirming the relationship between neurophysiological processes and language abilities, which allows for a deeper understanding of the nature of human speech activity.